2017
DOI: 10.1128/jvi.00764-17
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Highly Divergent Coronavirus in the Asian House Shrew from China Illuminates the Origin of the Alphacoronaviruses

Abstract: Although shrews are one of the largest groups of mammals little is known about their role in the evolution and transmission of viral pathogens including coronaviruses. We captured 266 Asian house shrews () in Jiangxi and Zhejiang provinces, China, during 2013-2015. Coronavirus (CoV) RNA was detected in 24 Asian house shrews, with an overall prevalence of 9.02%. Complete viral genome sequences were successfully recovered from the RNA positive samples. The newly discovered shrew CoV fell into four lineages refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 45 publications
0
50
0
1
Order By: Relevance
“…We surveyed 462 rodents from 8 species and 148 Asian house shrews from Zhejiang province. Although our previous studies have demonstrated the extensive diversity of a broad range of viruses (arenaviruses, coronaviruses, hantaviruses, rotaviruses) in rodents and shrews from Longquan and Wenzhou in Zhejiang province (Li et al, , 2016Wang et al, 2015, 2017bLin et al, 2012, no hepadnavirus was identified in these small mammals, even though these viruses are presentin the bats sampled from the same location (i.e. Longquan).…”
Section: Discussionmentioning
confidence: 85%
“…We surveyed 462 rodents from 8 species and 148 Asian house shrews from Zhejiang province. Although our previous studies have demonstrated the extensive diversity of a broad range of viruses (arenaviruses, coronaviruses, hantaviruses, rotaviruses) in rodents and shrews from Longquan and Wenzhou in Zhejiang province (Li et al, , 2016Wang et al, 2015, 2017bLin et al, 2012, no hepadnavirus was identified in these small mammals, even though these viruses are presentin the bats sampled from the same location (i.e. Longquan).…”
Section: Discussionmentioning
confidence: 85%
“…The 450 species in the order suggest a smaller genetic diversity as compared to the orders Rodentia and Chiroptera with 2269 and 1241 species, respectively. Nevertheless, surprisingly diverse alpha-and betacoronaviruses were detected in Eulipotyphla, including viruses clustering with important CoV clades such as MERS-CoV (Corman et al, 2014c;Tsoleridis et al, 2016;Wang et al, 2017). Other CoVs in shrews and hedgehogs are genetically equidistant and represent relatively deep lineages in the phylogenetic tree.…”
Section: Perspectivesmentioning
confidence: 99%
“…SeACoV shared 95% nucleotide (nt) sequence identity with the bat CoV HKU2 strains and 96-98% nt identity with the HKU2-derived bat SADSrelated coronavirus (SADSr-CoV) strains at the complete genome level Zhou et al, 2018). Interestingly, SeACoV and other HKU2-related α-CoVs possess the unique S genes closely related to the betacoronavirus (β-CoV), in a manner similar to those by rodent and Asian house shrew α-CoVs (Tsoleridis et al, 2019;Wang et al, 2015Wang et al, , 2017b, suggesting the occurrence of ancient recombination events https://doi.org/10.1016/j.virol.2019.08.006 Received 30 May 2019; Received in revised form 8 August 2019; Accepted 8 August 2019 between α-CoV and β-CoV (Lau et al, 2007;Pan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%